FROM HISTORY OF ARTISTICALLY-PEDAGOGICAL EDUCATION: TEACHING OF DISCIPLINES OF GRAPHIC CYCLE IN UKRAINE XIX ARE OF THE XX CENTURY - I.O. Krasyuk (Academy of Cognitive and Natural Sciences, 2022)
In the article the state of teaching of graphic disciplines is examined in domestic school formation of the adopted epoch. On the basis of review of normative documents leading tendencies and methodical Iuims of educational process and requirement to the teachers of drawing are traced.